Resolusi Konflik Antar Organ Pengurus Yayasan: Studi Kasus Konflik Yayasan Pendidikan Al-Ijtihad Kota Tangerang - Ismail, Azizah; Soetrisna, Denny; Setiawan, Rizki (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2024)
This research uses Lewis Coser's Social Conflict theory by focusing on the conflict resolution process in the world of educational organizations or foundations. The approach used in this research is a qualitative approach and case study method. The researcher focuses on the course of the conflict involving various parties within the foundation, as well as resolution as an effort to resolve the conflict. Data collection in this research was carried out using in-depth interviews with parties involved in the conflict, analysis of related documents, and direct observation. The results of the research show that the factors that trigger conflict at YAPENSI Al-Ijtihad are differences in interests between its management organs, as a result of which it has the impact of conflict on the foundation with losses experienced by the Foundation. As a resolution effort to achieve a resolution of the conflict YAPENSI brought this conflict into the realm of law to prevent a bigger conflict. This research provides in-depth insight into the dynamics of conflict in educational foundations and the importance of conflict resolution to maintain the stability and smooth operation of foundations.